2017
DOI: 10.4314/sajas.v47i6.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of freezer storage on quality of <i>M. longissimus lumborum</i> from fallow deer (<i>Dama dama</i> L.)

Abstract: The aim of this study was to analyse changes in the quality of meat (M. longissimus lumborum) from 11 fallow deer (Dama dama L.) bucks, which had been deep-frozen (-26 °C) for 10 months. The proximate chemical composition, physico-chemical properties and sensory properties of the meat were analysed. Fallow deer aged 17-18 months were hunter-harvested in north-eastern Poland in November and December of the same hunting season. The results revealed that freezer storage did not influence the proximate chemical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
3
3
1
Order By: Relevance
“…In our study, meat samples were vacuum-packaged before freezing, which could contribute to an absence of changes in TBARS values during storage. is is consistent with the findings of Daszkiewicz et al [28] who demonstrated that storage in the freezer had no significant influence on TBARS values in vacuum-packaged fallow deer meat. Farouk and Freke [27] also reported that malondialdehyde concentration was lower in samples of red deer meat which were vacuum-packaged and stored in the freezer than in samples that were not vacuum-packaged (the latter were placed in bags of the same type as those used for vacuum packaging, except that the seals were broken to permit free exchange of air between the inside and outside of the packaging).…”
Section: Ph Valuesupporting
confidence: 93%
See 4 more Smart Citations
“…In our study, meat samples were vacuum-packaged before freezing, which could contribute to an absence of changes in TBARS values during storage. is is consistent with the findings of Daszkiewicz et al [28] who demonstrated that storage in the freezer had no significant influence on TBARS values in vacuum-packaged fallow deer meat. Farouk and Freke [27] also reported that malondialdehyde concentration was lower in samples of red deer meat which were vacuum-packaged and stored in the freezer than in samples that were not vacuum-packaged (the latter were placed in bags of the same type as those used for vacuum packaging, except that the seals were broken to permit free exchange of air between the inside and outside of the packaging).…”
Section: Ph Valuesupporting
confidence: 93%
“…A negative correlation between meat juiciness and cooking loss was also reported by other authors, including Aaslyng et al [40] and Jung et al [41]. Daszkiewicz et al [28] demonstrated that thawed fallow deer meat was less juicy than fresh meat.…”
Section: Shear Force and Sensory Evaluationsupporting
confidence: 61%
See 3 more Smart Citations